IRESite--a tool for the examination of viral and cellular internal ribosome entry sites - Mokrejs, Martin; Masek, Tomás; Vopálensky, Václav; Hlubucek, Petr; Delbos, Philippe; Pospísek, Martin (Nucleic acids research, 2010)
The IRESite (http://www.iresite.org) presents carefully curated experimental evidence of many eukaryotic viral and cellular internal ribosome entry site (IRES) regions. At the time of submission, IRESite stored >600 records. The IRESite gradually evolved into a robust tool providing (i) biologically meaningful information regarding the IRESs and their experimental background (including annotation of IRES secondary structures and IRES trans-acting factors) as well as (ii) thorough concluding remarks to stored database entries and regularly updated evaluation of the reported IRES function. A substantial portion of the IRESite data results purely from in-house bioinformatic analyses of currently available sequences, in silico attempts to repeat published cloning experiments, DNA sequencing and restriction endonuclease verification of received plasmid DNA. We also present a newly implemented tool for displaying RNA secondary structures and for searching through the structures currently stored in the database. The supplementary material contains an updated list of reported IRESs.
Keywords: Software; software; RNA virová; Humans; databáze genetické; ribozomy; Sequence Analysis, DNA; genom virový; iniciace translace peptidového řetězce; Information Storage and Retrieval; lidé; plazmidy; zvířata; Ribosomes; výpočetní biologie; sekvenční analýza DNA; Computational Biology; internet; Genome, Viral; Internet; konformace nukleové kyseliny; Databases, Genetic; RNA, Viral; Nucleic Acid Conformation; databáze nukleových kyselin; Animals; Databases, Nucleic Acid; Plasmids; ukládání a vyhledávání informací; Peptide Chain Initiation, Translational